A rapid potentiometric titration method for measuring low-level chemical oxygen demand in organic wastewater containing synthetic phenothiazine dyes. Issue 16 (13th April 2018) - Cao, Xiaojuan; Zhou, Min; Ma, Yongjun; Liu, Fen; Yang, Ning; Xie, Yun
Abstract : An advanced sample treatment by combining microwave-assisted oxidation with two-step wet-chemical digestion for low-level COD analysis in dye-containing wastewater was developed. Abstract : In this work, we have developed a rapid determination method for the low-level chemical oxygen demand (COD) index in dye-containing wastewater samples, which is based on a novel sample treatment technique that combines the advantages of microwave-assisted digestion and two-step wet-chemical oxidation with two oxidants such as KMnO4 and Ce(SO4 )2 . By using methylene blue (MB) as the model dye molecule, we have optimized the determination conditions and affirmed the validity of the COD assay for dye-containing wastewater. In particular, specific molar proportion relationships have been found between the added amounts of oxidants and catalysts in two kinds of digestion solutions, which exist as n (KMnO4 ) : n (MnSO4 ) = 6 : 1 and n (Ce(SO4 )2 ) : n (Cu 2+ + Ag + ) = 4 : 3. Additionally, potassium tungstate as a specific reagent is introduced into the wet-chemical digestion reaction of water samples for the first time, and its positive influence on COD determination is investigated. Under optimized operating conditions, the average digestion efficiency of the MB molecule in a standard dye sample is up to 99.5%. The COD quantitative range of the MB dye is 1.0–75.0 mg O2 L −1 with a correlation coefficient ( R 2 ) of 0.9996 and a lower limit of detection (LOD) of 0.33 mg O2 per L (3 σ ). Moreover, the application of the method to another three types of phenothiazine dyes has also achieved satisfactory results.